2001
DOI: 10.1006/dbio.2001.0351
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Heparin-Binding EGF-like Growth Factor and Its Processing by Metalloproteinases in Early Epithelial Morphogenesis of the Submandibular Gland

Abstract: In the present study, the role of a member of the epidermal growth factor (EGF) family, heparin-binding EGF-like growth factor (HB-EGF), in organ development was investigated by using developing mouse submandibular gland (SMG), in which the EGF receptor signaling and heparan sulfate chains have been implicated. HB-EGF mRNA was detected in developing SMG by RT-PCR analysis and was expressed mainly in epithelium and weakly in mesenchyme of the embryonic SMG. Epithelial morphogenesis was inhibited by a synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 29 publications
2
65
0
Order By: Relevance
“…It is possible that the time lag might represent the time necessary to synthesize the autocrine factor that functions like EGF in FGF7-alone cultures. In fact, submandibular epithelium synthesizes a heparinbinding EGF-like growth factor in vivo, which appears to be involved in epithelial branching (Umeda et al, 2001). Furthermore, it is noteworthy that the effective concentration of EGF decreased to one tenth in the presence of FGF7 (Morita and Nogawa, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the time lag might represent the time necessary to synthesize the autocrine factor that functions like EGF in FGF7-alone cultures. In fact, submandibular epithelium synthesizes a heparinbinding EGF-like growth factor in vivo, which appears to be involved in epithelial branching (Umeda et al, 2001). Furthermore, it is noteworthy that the effective concentration of EGF decreased to one tenth in the presence of FGF7 (Morita and Nogawa, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The salivary epithelium thereby was proved to perform branching morphogenesis when embedded in a laminin-rich basementmembrane-like matrix and stimulated by epidermal growth factor (EGF; Nogawa and Takahashi, 1991). Since then, many studies have reported the involvement of EGF family ligands (transforming growth factor ␣, heparin-binding EGF, and neuregulin) and laminins in the branching morphogenesis of the salivary gland (Kadoya et al, 1995;Kashimata and Gresik, 1997;Hosokawa et al, 1999;Kashimata et al, 2000;Umeda et al, 2001;Koyama et al, 2003;Miyazaki et al, 2004;Kadoya and Yamashina, 2005). During the development of the mesenchyme-free culture of salivary epithelium, we introduced a serum-supplemented medium but paid little attention to the serum, because we had typically added serum as a source of nutrients for in vitro organ cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction encompasses sequential events directed by diffusible factors and extracellular matrices 34) . Therefore, the presence of endogenous extracellular matrix (ECM) and diffusible factors is pivotal for tissue morphogenesis [35][36][37] . In our system, the expression of FGF and Twist1 in epithelialmesenchymal interface suggests that the morphogenesis of epithelial tissue is maintained in a native manner.…”
Section: Discussionmentioning
confidence: 99%
“…The SMG rudiments at E13 were dissected in Hanks' balanced salt solution (Umeda et al, 2001). The rudiments were placed on Millipore filters and cultured for 12 hr with DMEM/ 10% FCS containing 0.3mM of CKI7 (Seikagaku Kogyo, Japan) dissolved in dimethyl sulfoxide.…”
Section: Organ Culturementioning
confidence: 99%